Design and Experiment of Mobile Assistant Robot for the Semi Disabled Elderly - Gang Li; Yujuan Wang; Fengwen Lan; Zhenjun Du; Bing Guo; Qiancheng Sun (Jixie chuandong)
In order to solve the movement dysfunction problem of the lower limbs caused by the decline of muscle strength of the lower limbs， bone and joint diseases， cardiovascular and cerebrovascular diseases， spinal cord injury， etc.， such as the inability to independently complete the basic life actions such as walking， standing， sitting， etc.， a mobile assisted robot structure design scheme with the functions of assisted walking， assisted seating， assisted moving is proposed. According to the size distribution of human body， the size of structural components is calculated. In order to ensure that the mechanism has enough structural strength， the finite element simulation analysis of key components is carried out. On this basis， human-machine coupling system model is established， and kinematics simulation of human-machine coupling is completed. Hardware system design scheme of mobile assisted robot is proposed. Electrical system connection is built， and hardware circuit design is completed. In order to verify the correctness of the theoretical results， the experimental prototype is manufactured and related experiments are carried out.